1995
DOI: 10.1161/01.cir.91.4.1182
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Wine and Grape Juice Inhibits In Vivo Platelet Activity and Thrombosis in Stenosed Canine Coronary Arteries

Abstract: Pure ethanol has been shown to inhibit platelet aggregation in vitro, ex vivo, and in vivo, although a blood alcohol content (BAC) of > or = 0.2 g/dL is usually required. The BAC of dogs administered the red wine-saline solution intravenously was 0.028 g/dL, much less than is usually necessary for platelet inhibition with pure ethanol. Because red wine and grape juice, but not white wine, abolished the CFRs, this suggests there are compounds present in red wine and grape juice that are not present or are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
190
1
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(202 citation statements)
references
References 31 publications
6
190
1
4
Order By: Relevance
“…43,44 This is particularly so for red wine, 7,44 which, unlike white wine, has been shown in several studies 43,44 to be an effective inhibitor of platelet aggregation. The epidemiological evidence that red wine is more beneficial than other alcoholic beverages, however, is not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 This is particularly so for red wine, 7,44 which, unlike white wine, has been shown in several studies 43,44 to be an effective inhibitor of platelet aggregation. The epidemiological evidence that red wine is more beneficial than other alcoholic beverages, however, is not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids protect low-density lipoproteins from oxidation, attenuate atherosclerosis, have anti-inflammatory effects and may inhibit platelet activity (Demrow et al, 1995;Chopra and Thurnham, 1999;Mruk et al, 2000;Fuhrman and Aviram, 2001;Kris-Etherton et al, 2004). No previous epidemiologic study has evaluated the association of flavonoid intake with PAOD, but several investigations have pointed to an inverse association of these compounds with coronary heart disease (Huxley and Neil, 2003;Lagiou et al, 2004), another manifestation of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Red wine has been assumed to account for the phenomenon, which is known as the "French paradox." 1 Recently, it has been demonstrated that red wine polyphenols (RWPs) have various antiatherogenic effects, such as antioxidation of LDL-cholesterol, 2,3 inhibition of adhesion molecule expression in cytokine-stimulated vascular endothelial cells (ECs), 4 inhibition of platelet aggregation, 5 induction of NO release, and vasorelaxation. 6 It has been shown that development of atherosclerosis is characterized by EC dysfunction, proliferation and migration of vascular smooth muscle cells (SMCs), and increased extracellular matrix deposition.…”
mentioning
confidence: 99%